Adaptive research for grain production (BRUMDEC) (A short term programme) - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2021)
54 páginas. Series Miscellaneous Publication N. 317.